Analisis Kualitatif atas Kontribusi Perbankan Syariah terhadap Stabilitas Keuangan: Studi Kasus Bank Syariah Indonesia (BSI) - Revita Pratama Putri; Anggun Okta Fitri (Jurnal Bersama Ilmu Ekonomi (EKONOM), 2025)
This study aims to analyze the contribution of Bank Syariah Indonesia (BSI) to national financial stability through a qualitative case study approach. The research focuses on liquidity management, risk management, and compliance with Sharia principles. The findings indicate that BSI plays a strategic role in enhancing the resilience of the national financial system through adaptive and sustainability-oriented management strategies. These include portfolio diversification in productive sectors—particularly micro, small, and medium enterprises (MSMEs)—optimization of banking service digitalization, and the strengthening of governance based on Sharia values.Compliance with Sharia principles not only ensures operational integrity but also reinforces public trust in Islamic banking institutions. The implementation of asset-based financial systems and the avoidance of speculative practices significantly contribute to mitigating systemic risks. Moreover, BSI’s efforts to promote financial inclusion and increase public literacy regarding Sharia-compliant financial products further support the overall stability of the financial system.Nonetheless, several challenges remain, such as the low level of financial literacy among the general public and intense competition with conventional banks. Therefore, strategic and collaborative efforts are needed among regulators, industry players, and the public to enhance understanding and confidence in the Islamic financial system. These findings underscore the substantial potential of BSI in supporting the long-term stability and sustainability of Indonesia’s financial system.